Pseudoaneurysm and renal arteriovenous fistula after nephrectomy: two cases treated by transcatheter coil embolization - Bozgeyik, Zulkif; Ozdemir, Huseyin; Orhan, Irfan; Cihangiroglu, Mutlu; Cetinkaya, Ziya (Springer Heidelberg, 2008)
Pseudoaneurysms and arteriovenous fistulas of renal arteries are rare clinical lesions. Invasive renal procedures may lead to pseudoaneurysm or arteriovenous fistulas (AVFs). We report two pseudoaneurysms and arteriovenous fistula cases that were treated by transcatheter embolization with metallic coils. The first case is left main renal artery pseudoaneurysm after nephrectomy in a patient with a solid renal tumor. The second case is right main renal artery AVF with giant pseudoaneurysm after both gunshot injury and nephrectomy. On the basis of color Doppler sonography and computed tomography (CT) findings, cases were diagnosed as pseudoaneurysm after nefrectomy. Contrast-enhanced CT scans showed a hyperdense area within the hematoma consistent with pseudoaneurysm. Endovascular treatment with coil embolization succeeds to total occlusion in renal artery pseudoaneurysm. Delayed hemorrhage related to postnephrectomy may be life-threatening conditions because of diagnostic difficul-ties. AVF and pseudoaneurysm can be treated safely and successfully by transcatheter arterial embolization.
Keywords: Pseudoaneurysm; Arteriovenous fistula; Nephrectomy; Coil embolization; Computed tomography